2022
DOI: 10.1002/1348-9585.12313
|View full text |Cite
|
Sign up to set email alerts
|

Treatment interruption is a risk factor for sickness presenteeism: A large-scale cross-sectional study during the COVID-19 pandemic

Abstract: Objectives This study examined the relationship between interruption to routine medical care during the coronavirus disease 2019 pandemic and sickness presenteeism among workers in Japan. Methods A cross‐sectional study using data obtained from an internet monitor questionnaire was conducted. Interruption to medical care was defined based on the response “I have not been able to go to the hospital or receive treatment as scheduled.” The fraction of sickness presenteeism… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Four studies had been conducted in Japan ( 31–34 ) and 4 in United Kingdom ( 35–38 ), 3 in United States ( 39–41 ), 2 in China ( 42 , 43 ), Germany ( 44 , 45 ), and the Republic of Korea ( 46 , 47 ), and 1 in Sweden ( 16 ), Wales ( 48 ), Canada ( 22 ), Turkey ( 49 ), Lithuania ( 50 ), Portugal ( 51 ), Australia and New Zealand ( 52 ), and Belgium and the Netherlands ( 53 ). In 14 of the 25 selected articles, collection took place in 2020; 6 of the 25 were collected in 2021; and the remaining 5 were collected over months in both 2020 and 2021.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies had been conducted in Japan ( 31–34 ) and 4 in United Kingdom ( 35–38 ), 3 in United States ( 39–41 ), 2 in China ( 42 , 43 ), Germany ( 44 , 45 ), and the Republic of Korea ( 46 , 47 ), and 1 in Sweden ( 16 ), Wales ( 48 ), Canada ( 22 ), Turkey ( 49 ), Lithuania ( 50 ), Portugal ( 51 ), Australia and New Zealand ( 52 ), and Belgium and the Netherlands ( 53 ). In 14 of the 25 selected articles, collection took place in 2020; 6 of the 25 were collected in 2021; and the remaining 5 were collected over months in both 2020 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…There are some high-pressure work environments, such as that of the study by Jia et al ( 42 ), carried out on a sample of 4,261 medical staff, in which it was observed that in high-pressure environments, health problems are more likely to appear and medical staff are more likely to ignore their own health problems, thus increasing sickness presenteeism. In addition to the field of healthcare, it has been observed that the shift from face-to-face work to teleworking has led to workers being forced to be constantly online and on email, thereby generating constant stress, as they worry about losing their jobs ( 35 ). For many workers, they had to stay online at all times to prove their worth at work or to convince their employers that they were not avoiding their duties while working from home ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even SMEs that had good cooperation with medical institutions by utilizing external resources and internal staff, such as coordinators of health promotion and employment support, access to medical institutions is clearly dif-ficult due to COVID-19, which influences the provision of support for the balance between medical treatment and work. Okawara et al reported that approximately 4% of workers experienced interrupted medical care during the COVID-19 pandemic 22) . Interruption of medical care can adversely influence the management of chronic diseases and delay the detection and treatment of new diseases 23) .…”
Section: Discussionmentioning
confidence: 99%
“…Telecommuting not only blurs the distinction between work and personal life but also makes it harder for managers to monitor the health of their employees. In some cases, lack of access to medical resources [ 35 ] and increased treatment interruption [ 36 ] may exacerbate chronic diseases. This may consequently lead to an increased prevalence of presenteeism in CKD patients compared to that before the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%